Post‐traumatic stress symptoms among mothers of children with leukemia undergoing treatment: a longitudinal study. Issue 6 (9th July 2012) - Tremolada, Marta; Bonichini, Sabrina; Aloisio, Donatella; Schiavo, Simone; Carli, Modesto; Pillon, Marta
Abstract Objective To assess post‐traumatic stress symptoms (PTSS) in mothers of children over 2 years of leukemia treatment, to identify possible early family and child predictors of this symptomatology and to indicate the temporal trajectory of PTSS. Methods Participants were 76 Italian mothers (mean age = 37.30 years; SD = 6.07) of children receiving treatment for acute lymphoblastic (n = 69) or myeloid (n = 7) leukemia. Mothers had 12.05 years of education (SD = 3.87), and their incomes were average (52.1%), high (26%) and low (21.9%) for Italian norms, never in poverty. The pediatric patients with leukemia were equally distributed by gender with their mean age of 7.10 years (SD = 4.18). Post‐traumatic stress symptoms were measured by a 17‐item checklist. Scales assessing anxiety, depression, physical (Brief Symptom Inventory 18) and cognitive functioning (Problem Scale), and life evaluation were also used. There were five assessment points: 1 week (T1), 1 month (T2), 6 months (T3), 12 months (T4) and 24 months post‐diagnosis (T5). Results The main results indicated moderate presence of clinical PTSS (≥9 symptoms: 24% at T2, 18% at T3, 16% at T4 and 19% at T5) that remained stable across time points, whereas Brief Symptom Inventory 18 Global score decreased and life evaluation improved. A series of hierarchical regression models identified cognitive functioning early after the diagnosis as the best predictive factor of PTSS across time points. Conclusion Specific psychological interventions could be devised for mothers at risk for short and long‐term PTSS just after the diagnosis. Copyright © 2012 John Wiley & Sons, Ltd.